2023
DOI: 10.3389/fnagi.2023.1138336
|View full text |Cite
|
Sign up to set email alerts
|

The fusiform gyrus exhibits differential gene-gene co-expression in Alzheimer's disease

Abstract: Alzheimer's Disease (AD) is an irreversible neurodegenerative disease clinically characterized by the presence of β-amyloid plaques and tau deposits in various regions of the brain. However, the underlying factors that contribute to the development of AD remain unclear. Recently, the fusiform gyrus has been identified as a critical brain region associated with mild cognitive impairment, which may increase the risk of AD development. In our study, we performed gene co-expression and differential co-expression n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…Several co-expression and differential co-expression network analyses have already been applied on RNA-seq data from hippocampus and fusiform gyrus, leading to the identification of co-expressed networks and genes associated with AD ( Sato et al, 2019 ; Crist et al, 2021 ; Xia et al, 2022 ; Ribeiro-dos-Santos et al, 2023 ). As our aim was the identification of lncRNAs that could take part of the pathologic molecular mechanisms of AD, we prioritized modules comprising the majority of lncRNAs which could be identified as driver genes and could be postulated to influence the expression of other genes or that could be directly involved in the causal mechanisms of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Several co-expression and differential co-expression network analyses have already been applied on RNA-seq data from hippocampus and fusiform gyrus, leading to the identification of co-expressed networks and genes associated with AD ( Sato et al, 2019 ; Crist et al, 2021 ; Xia et al, 2022 ; Ribeiro-dos-Santos et al, 2023 ). As our aim was the identification of lncRNAs that could take part of the pathologic molecular mechanisms of AD, we prioritized modules comprising the majority of lncRNAs which could be identified as driver genes and could be postulated to influence the expression of other genes or that could be directly involved in the causal mechanisms of AD.…”
Section: Discussionmentioning
confidence: 99%
“…The last model we will discuss was suggested by our lab [21] and proposes that, by localizing at the ER thanks to interaction with fibronectin type III domain containing 3A and 3B (FNDC3A and FNDC3B) [21,66], two proteins known to be involved in cell development [76,77], but also with disease [78,79], and specifically cancer [80][81][82][83][84][85], FAM46C regulates intracellular trafficking (Figure 1C). In our work, we found that expression of FAM46C in MM cell lines was coupled with only a really mild alteration of RNA levels and a really weak poly(A) activity, comparable to that of the loss-of-function FAM46C variant D90G.…”
Section: Fam46c As a Regulator Of Intracellular Trafficking Dynamicsmentioning
confidence: 99%